KONSERVASI MATA AIR DAN PENJERNIHAN AIR BERBAHAN FILTER ORGANIK DI DESA PANA, KECAMATAN ALLA, KABUPATEN ENREKANG: tidak ada - Muhammad Hamzah Syahruddin; Amiruddin; Halmar Halide; Sakka; Hasniati (LP2M Universitas Hasanuddin, 2024)
The springs included in the administrative area of ​​Pana Village are waibuktu, wailandan, waidollok, waiallak, and waipana. Pana Village is also crossed by two rivers, namely the Mata Allo River and the Salu Dollok River. The springs and rivers in Pana Village have not been managed in an integrated manner, so the people of Pana Village have difficulty getting water, especially during the dry season. Therefore, conserving springs in Pana Village is important to maintain the existence and sustainability of springs in the area. Conservation of the Pana Village spring needs to be done because the upstream water catchment area continues to develop as agricultural land and settlements, so it can potentially damage the spring catchment area. The conservation of springs in Pana Village is carried out by making rectangular cube biopore infiltration wells to increase water absorption into the soil. Active participation of the community in constructing rectangular cube biopore recharge wells so that water is always available during the dry season in terms of quality and quantity. In addition, through the community service program from the Department of Geophysics, UNHAS conducts outreach to the people of Pana Village so that the community's active participation preserves the environment and springs and river resources. Conservation of springs in Pana Village is carried out by introducing the community to conservation technologies that can be used. Conservation technology includes greening water catchment areas, making cubical biopore infiltration holes, and training in making water purification equipment made from organic filters. The training participants have understood the existence of groundwater and its conservation above 97%. They can conserve groundwater springs by making cubic biopore infiltration holes (LRBK) and can use water purification tools made from organic filters (PABFO). — Mata air yang masuk dalam wilayah administrative Desa Pana adalah waibuktu, wailandan, waidollok, waiallak, dan waipana. Desa Pana juga dilewati dua sungai yaitu sungai mata allo dan sungai salu dollok. Mata air dan sungai di desa pana belum dikelola secara terintegrasi sehingga masyarakat Desa Pana kesulitan air terutama pada musim kemarau. Oleh karena itu Konservasi mata air di Desa Pana adalah usaha yang penting dilakukan untuk mempertahankan keberadaan serta keberlanjutan mata air di daerah tersebut. Konservasi mata air Desa Pana perlu dilakukan karena daerah hulu resapan air terus berkembang sebagai lahan pertanian dan pemukiman sehingga berpotensi merusak daerah resapan mata air. Konservasi mata air di Desa Pana dilakukan dengan membuat sumur resapan biopori kubus persegi panjang untuk meningkatkan resapan air ke dalam tanah. Partisipasi aktif masyarakat dalam membuat sumur respan biopori kubus persegi panjang agar senantiasa air tersedia pada musim kemarau baik dalam hal kualitas maupun kuntitasnya. Selain itu melalui program pengabdian kepada masyarakat dari Departemen geofisika UNHAS melakukan penyuluhan kepada masyarakat Desa Pana agar partisipasi aktif masyarakat melestarikan lingkungan hidup dan sumber daya mata air dan sungai. Konservasi mata air di Desa Pana dilakukan dengan memperkenalkan kepada masyarakat teknologi konservasi yang dapat digunakan. Teknologi konservasi meliputi mnghijaukan daerah tangkapan air, pembuatan lubang resapan biopori kubus dan pelatihan pembuatan alat penjernihan air berbahan filter organik. Peserta pelatihan telah memahami keberadaan air tanah dan konservasinya diatas 97% dan mampu melakukan konservasi mata air tanah dengan membuat lubang resapan biopori kubus (LRBK) dan mampu membuat alat penjernihan air berbahan filter organik (PABFO).